Cuatro inscripciones pertenecientes al antiguo Convento de San Vicente de Villamayor de los Montes - Alejandro García Morilla (Medievalista)
The epigraphic group presented here belongs to the old monastery of St. Vicente de Villamayor de los Montes and is kept in the cloisters of the present Cistercian temple. It represents a primary historiographic source to rebuild its historical past from a scriptural and advertising perspective. This four-inscription group constitutes one of the few vestiges preserved from the early monastery of Villamayor.Here we study this corpus through the modern Spanish epigraphic method used for the edition of the Corpus Inscriptionum Hispaniae Mediaevalium, in order to present a critical and scientific study of this group which could allow us to go deep into the particularities of this advertising activity – that is what inscriptions are – and the purpose which these epigraphs may have had, as well as for a better knowledge of the society which created them. To achieve that, we shall address the study of the genesis or elaboration of these inscriptions as well as the analysis of the outer, inner and functional characters, and dwell on the epigraphic tradition and its upkeep.